AP2M1 mediates autophagy-induced CLDN2 (claudin 2) degradation through endocytosis and interaction with LC3 and reduces intestinal epithelial tight junction permeability. Issue 9 (2nd September 2022) - Ganapathy, Ashwinkumar Subramenium; Saha, Kushal; Suchanec, Eric; Singh, Vikash; Verma, Aayush; Yochum, Gregory; Koltun, Walter; Nighot, Meghali; Ma, Thomas; Nighot, Prashant
ABSTRACT: The intestinal epithelial tight junctions (TJs) provide barrier against paracellular permeation of lumenal antigens. Defects in TJ barrier such as increased levels of pore-forming TJ protein CLDN2 (claudin-2) is associated with inflammatory bowel disease. We have previously reported that starvation-induced macroautophagy/autophagy enhances the TJ barrier by degrading pore-forming CLDN2. In this study, we examined the molecular mechanism underlying autophagy-induced CLDN2 degradation. CLDN2 degradation was persistent in multiple modes of autophagy induction. Immunolocalization, membrane fractionation, and pharmacological inhibition studies showed increased clathrin-mediated CLDN2 endocytosis upon starvation. Inhibition of clathrin-mediated endocytosis negated autophagy-induced CLDN2 degradation and enhancement of the TJ barrier. The co-immunoprecipitation studies showed increased association of CLDN2 with clathrin and adaptor protein AP2 (AP2A1 and AP2M1 subunits) as well as LC3 and lysosomes upon starvation, signifying the role of clathrin-mediated endocytosis in autophagy-induced CLDN2 degradation. The expression and phosphorylation of AP2M1 was increased upon starvation. In-vitro, in-vivo (mouse colon), and ex-vivo (human colon) inhibition of AP2M1 activation prevented CLDN2 degradation. AP2M1 knockout prevented autophagy-induced CLDN2 degradation via reduced CLDN2-LC3 interaction. Site-directed mutagenesis revealed that AP2M1 binds to CLDN2 tyrosine motifs (YXXФ) (67–70 and 148–151). Increased baseline expression of CLDN2 and TJ permeability along with reduced CLDN2-AP2M1-LC3 interactions in ATG7 knockout cells validated the role of autophagy in modulation of CLDN2 levels. Acute deletion of Atg7 in mice increased CLDN2 levels and the susceptibility to experimental colitis. The autophagy-regulated molecular mechanisms linking CLDN2, AP2M1, and LC3 may provide therapeutic tools against intestinal inflammation. Abbreviations: Amil: amiloride; AP2: adaptor protein complex 2; AP2A1: adaptor related protein complex 2 subunit alpha 1; AP2M1: adaptor related protein complex 2 subunit mu 1; ATG7: autophagy related 7; CAL: calcitriol; Cas9: CRISPR-associated protein 9; Con: control; CPZ: chlorpromazine; DSS: dextran sodium sulfate; EBSS: Earle's balanced salt solution; IBD: inflammatory bowel disease; TER: trans-epithelial resistance; KD: knockdown; KO: knockout; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MβCD: Methyl-β-cyclodextrin; MET: metformin; MG132: carbobenzoxy-Leu-Leu-leucinal; MTOR: mechanistic target of rapamycin kinase; NT: non target; RAPA: rapamycin; RES: resveratrol; SMER: small-molecule enhancer 28; SQSTM1: sequestosome 1; ST: starvation; ULK1: unc-51 like autophagy activating kinase 1; WT: wild type.